Fair Business Leadership: Is Protecting Minority Investors Important to the Development of Start-Ups in Clean and Digital Energy? - Dmytro Halynskyi; Oleksandr Telizhenko (Business Ethics and Leadership)
The protection of minority investors is increasingly recognized as crucial for the growth of start-ups in the clean and digital energy sectors, which are central to advancing global sustainability goals. Start-ups in these sectors face unique challenges, including high capital requirements, evolving regulatory landscapes, and long development timelines, necessitating a supportive investment environment that fosters innovation and accountability. This study investigates the impact of minority investor protections on start-up growth, specifically examining the relationship between investor protection indices – such as the Extent of Shareholder Rights Index, Disclosure Index, and Corporate Transparency Index – and growth metrics, including the number of active start-ups and total funding across stages. With panel data from 19 countries over 7 years, this research applies three econometric models – the pooling model, fixed effects model, and random effects model – to capture the influence of investor protection on start-up growth while accounting for country- and time-specific variations. The models’ results show that stronger investor protections correlate positively with increased start-up activity; individual protection variables’ significance and explanatory power vary. The random effects model suggests that “Ease of Shareholder Suits” and “Extent of Shareholder Rights” exhibit borderline significance, indicating a weak yet potential influence on start-up growth. However, overall R-squared values remain low across all models, highlighting the likely role of other unobserved factors in shaping outcomes in the clean and digital energy sectors. These findings imply that while robust minority investor protections contribute to a favorable environment for start-ups, their direct impact on growth metrics may be limited. The study underscores the need for an integrated approach, where investor protections form part of a broader strategy encompassing regulatory support and economic incentives, to fully support the scalability and sustainability of start-ups committed to clean and digital energy innovation.